The Role of Language Corpora in Teaching English as a Foreign Language in Poland - Szudarski, Paweł (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2011)
The study is a corpus-informed experiment addressing the effects of explicit instruction on English language learners’ collocational competence. Two groups of L1 Polish learners of English as a foreign language received two different forms of teaching: enriched input (the enriched group) and enriched input plus chunking practice (the enriched plus group). The enriched input group read texts containing target collocations and completed exercises focused on general vocabulary whereas the enriched plus group read the same texts but the exercises they completed were specifically focused on collocations. The target collocations were verb-noun combinations with frequent delexical English verbs (‘give’, ‘take’, ‘have’, ‘make’, ‘do’) known to be causing difficulty in L2 production. Three tests tapping into collocational competence at different levels of vocabulary mastery revealed that learners in both groups improved their knowledge of the target collocations and the instruction in both groups was equally effective. The study is discussed in the context of the use of corpora in teaching English and offers insights into language pedagogy.
Keywords: The use of corpora in teaching English; teaching English as a foreign language; English Language Teaching; corpus linguistics; teaching and language corpora